NILAI YANG TERKANDUNG DALAM GAGURITAN MITUTURIN ANGGA - Ida Bagus Putu Eka Suadnyana (Sanjiwani: Jurnal Filsafat, 2018)
There is an inheritance of classical texts written in lontar leaves in the form of poetry and untold. Classical texts in the form of classified prose such as parwa, babad, speech, wariga and usadha. While the classical text in the form of poetry is classified as a form of script that uses songs such as: kakawin, kidung and gaguritan. Gaguritan Mituturin Angga is an essay that contains advice for yourself. The theory used to solve research problems is the theory of functional structure, and value theory. This research takes the form of a qualitative design with a phenomenological approach. Data is collected by using, literature studies, and text studies. After the data is collected, the data is analyzed with qualitative descriptive methods. Based on this analysis, the ethical value of Gaguritan Mituturin Angga emphasizes the importance of children showing an attitude of filial piety to parents and other creatures as an application process / practice of the teachings of Tri Kaya Parisudha. Social value Gaguritan Mituturin Angga emphasizes good behavior in life, especially when faced with complicated problems involving the social field, the value of yoga education emphasizes the control of the mind of all temptations both temptations of destiny and outward temptations of others, the value of wiweka emphasizes the ability to distinguish -different, weighing, and finally choosing between good and bad, and divine value emphasizing the importance of understanding and mastery of characters that build the human body as a form of identity, especially Hindus.